DEVELOPMENT OF ANTIOXIDANT ENRICHED GREEK YOGHURT USING SENNA AURICULATA FLOWER POWDER EXTRACT - P. Sivakumar; R. Ramachandran; K. Suvalakshmi (Indian Journal of Veterinary and Animal Sciences Research, 2026)
Greek yogurt is currently the largest growing sector in the dairy industry. Greek- style yogurt, also known as strained yogurt, concentrated yogurt or thick yogurt, is a semisolid fermented milk product derived from yogurt by draining away part of its whey. This study is aimed to develop an antioxidant-enriched Greek yoghurt by incorporating Senna auriculata flower powder extract as a natural functional ingredient. The product combines the rich nutritional profile of Greek yoghurt with the radioactive properties of Senna auriculata, known for its phytochemicals such as flavonoids, phenolic acids and tannins that exhibit strong antioxidant, anti-inflammatory and antimicrobial activities. Three formulations were prepared with 2%, 4% and 6% Senna auriculata extract, each containing 5% sugar to enhance sweetness, mouthfeel and flavour stability. Standard Greek yoghurt processing steps including pasteurization, homogenization, fermentation and chilling were followed to maintain’   quality and extend shelf life. All formulations along with a control sample without extract were evaluated for sensory characteristics and antioxidant activity. The incorporation of 4% Senna auriculata flower extract significantly enhanced the antioxidant activity of yogurt, as evidenced by the increase in DPPH radical scavenging activity from 18.25% in the control to 60.46% in the 4% Senna auriculata flower powder extract enriched sample. Sensory evaluation results revealed that the 4% extract formulation achieved the highest acceptability in terms of taste, texture and overall appeal. The findings suggest that incorporating Senna auriculata extract at an optimal concentration of 4% can enhance both the functional and sensory qualities of Greek yoghurt, offering a promising addition to the functional dairy product market.